Columbia University & Slavery - Columbia University - Department of History; Foner, Eric (2021)
"The Columbia University and Slavery project explores a previously little-known aspect of the university’s history – its connections with slavery and with antislavery movements from the founding of King’s College to the end of the Civil War." [self-description]